FACTORS ASSOCIATED WITH MEDICATION ADHERENCE IN HYPERTENSION IN THE NGLUWAR PUBLIC HEALTH CENTER IN MAGELANG REGENCY - Taufan Agung Wicaksono; Arwinda Nugraheni; Firdaus Wahyudi; Pipin Ardhianto (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2021)
Background: Adherence is an important matter in the succession of hypertension medication. Despite the fact, it was found that many with hypertension had not used antihypertension medications as prescribed.Objective: To acknowledge the factors correlated to antihypertension medication adherence.Method: We used an observational, cross-sectional study model with a quantitative analytical approach. Some 131 qualified hypertensive patients of Ngluwar Public Health Center were recruited in February and March of 2021. A sampling method of purposive sampling was used. The data obtained were statistically analyzed using the chi-square test. Results: Eighty-two respondents (62.6%) had high medication adherence and 49 respondents (37.4%) were low at medication adherence. The statistical analysis results are as follows. Level of education (p = 0.374, PR = 1.264, CI 95% = 0.765-2.090), job status (p = 0.025, PR = 0.591, CI 95% = 0.367-0.953), comorbidity (p = 0.366, PR = 1.239, CI 95% = 0.772-1.988), duration of hypertension (p = 0.604, PR = 1.124, CI 95% = 0.722-1.751), family support (p = 0.142, PR = 1.396, CI 95% = 0.890-2.190), health worker support (p = 0.002, PR = 1.994, CI 95% = 1.313-3.028), affordability (p = 0.329, PR = 1.246, CI 95% = 0.802-1.937) and accessibility (p = 0.564, PR = 1.240, CI 95% = 0.623-2.468), and polypharmacy (p = 0.573, PR = 0.848, CI 95% = 0.488-1.474).Conclusion: Job status and health worker support were significantly correlated to antihypertensive medication adherence.